Temperature effects on buckling and vibration characteristics of sandwich plate with viscoelastic core and functionally graded material constraining layer. (May 2019) - Joseph, Shince V; Mohanty, SC
This article deals with the buckling and free vibration analysis of a sandwich plate with viscoelastic core and functionally graded material constraining lamina under high temperature environment. The first-order shear deformation theory is used for the finite element formulation of the plate. Along with the shear deformation, the longitudinal and transverse deformation of the core is also taken into account. The rise in the external temperature is found to reduce the critical buckling loads and fundamental frequencies, and to increase the corresponding modal loss factors. Various parametric studies such as effect of aspect ratio, core thickness ratio and volume fraction index on static and dynamic behaviour of the sandwich plate are also examined.